Multicenter, randomized, tandem evaluation of EndoRings colonoscopy – results of the CLEVER study - Dik, Vincent K.; Gralnek, Ian M.; Segol, Ori; Suissa, Alain; Belderbos, Tim D. G.; Moons, Leon M. G.; Segev, Meytal; Domanov, Sveta; Rex, Douglas K.; Siersema, Peter D. (Endoscopy, 2015)
Background and study aims: Adenoma miss rate during colonoscopy has become a widely acknowledged proxy measure for post-colonoscopy colorectal cancer. Among other reasons, this can happen because of inadequate visualization of the proximal aspects of colonic folds and flexures. EndoRings (EndoAid Ltd., Caesarea, Israel) is a silicone-rubber device that is fitted onto the distal end of the colonoscope. Its flexible circular rings engage and mechanically stretch colonic folds during withdrawal. The primary aim of this study was to compare adenoma miss rates between standard colonoscopy and colonoscopy using EndoRings.Methods: In this multicenter, randomized, tandem colonoscopy study, we performed same-day, back-to-back colonoscopies with EndoRings followed by standard colonoscopy, or vice versa.Results: After exclusion of 10 patients for protocol violations, 116 patients (38.8 % female; mean age 58.7) remained for analysis. The adenoma miss rate of EndoRings colonoscopy (7/67; 10.4 %) was significantly lower (P < 0.001) compared with standard colonoscopy (28/58; 48.3 %). Similar results were found for polyp miss rates: EndoRings (9.1 %) and standard colonoscopy (52.8 %; P < 0.001). Mean cecal intubation times (9.3 vs. 8.4 minutes; P = 0.142) and withdrawal times (7.4 vs. 7.2 minutes; P = 0.286), respectively, were not significantly different between EndoRings and standard colonoscopy. Mean total procedure time was longer with EndoRings than with standard colonoscopy (21.6 vs. 18.5 minutes, P = 0.001) as more polyps were removed.Conclusions: This study demonstrates that colonoscopy with EndoRings has lower adenoma and polyp miss rates than standard colonoscopy, which may improve the efficacy particularly of screening and surveillance colonoscopies.ClinicalTrials.gov NCT01955122.